Preventive Measures against Glazed Frost - I. I. Leonovich; D. D. Selioukov; A. V. Tsybulsky (Наука и техника)
The paper examines the method for calculation of technical salt consumption which is used for preventive treatment of highways and roads. This measure is intended for prevention of glazed frost on the highway and road surface for forecast rate of glazed frost build-up in the case of frozen fall-outs in the form of rain, drizzle or mist.